Aktivitas Antibakteri Ekstrak Etanol Daun Gamal (Gliricidia sepium) pada Berbagai Konsentrasi terhadap Pertumbuhan Bakteri Streptococcus mutans secara In-Vitro - Ni Luh Budi Artaningsih; Nur Habibah; Mastra Nyoman (Jurnal Kesehatan, 2018)
Streptococcus mutans is a positive gram bacteria which cause dental caries. From the several previous studies, Gamal leaf has been predicted as the antibacterial agent because of their active substance such as tannins, alkaloids, saponins, and flavonoids. The objective of the study was to know the antibacterial activity of ethanol extract of Gamal leaf (Gliricidia sepium) for Streptococcus mutans in various concentrations. This study was a true experimental with post-test only control design. The determination of antibacterial activity in this study was conducted by using Kirby Bauer disk diffusion method with the various concentrations, there were 40, 50, 60, 70 and 80%. The positive and negative controls in this study were 30 µg disk diffusion of chloramphenicol and the 96% of ethanol. The average inhibition of zone diameter in the concentrations of 40, 50, 60, 70 and 80% were 11.3, 12.3, 13.4, 15.3 and 19.2 mm, respectively. One Way ANOVA statistical analysis showed that the value of p was 0.000, so there was a difference of growth inhibition zone of Streptococcus mutans in various concentrations of ethanol extract of Gamal leaf (Gliricidia sepium). Based on the result, it can be concluded that the ethanol extract of Gamal leaf (Gliricidia sepium) have strong antibacterial activity, especially to Streptococcus mutans bacteria.